2015
DOI: 10.1111/liv.13036
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir‐based regimens in clinical practice achieve SVR rates closer to clinical trials: results from ERCHIVES

Abstract: Sofosbuvir-based regimens in clinical practice are associated with SVR rates comparable to those seen in clinical trials and low rates of grade 3/4 haematological adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 20 publications
6
39
0
Order By: Relevance
“…To date, there is very few data on the impact of GA on virological response to new DAA. Preliminary results suggest that the presence of diabetes does not appear to be predictive of treatment failure in G1 patients[46,47]. Further studies are needed to confirm these data and to evaluate the impact of DM on SVR in patients without poor prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is very few data on the impact of GA on virological response to new DAA. Preliminary results suggest that the presence of diabetes does not appear to be predictive of treatment failure in G1 patients[46,47]. Further studies are needed to confirm these data and to evaluate the impact of DM on SVR in patients without poor prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in Taiwan, 16.5% of study participants seropositive for HCV had CKD [1], while a US study found the unadjusted prevalence of HCV infection in patients receiving hemodialysis to be 14.4% [14]. Similarly, a recent study of HCV patients reported 14.4% had stage 3–5 CKD [34]. Patients with more advanced CKD have higher rates of HCV infection, with one study reporting a prevalence of 8.5% in those with stage 1 CKD and 14.5% in those with stages 4–5 [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, over 90% of the patients in this study were male, a large proportion had advanced liver disease by FIB-4, and the regimens did not include SOF/LDV that may make these findings less generalizable [23]. In contrast, another study from the VA population of over four thousand patients with genotypes 1–4 that included SOF/LDV regimens along with the other regimens reported by Backus et al, showed higher response rates of over 90% among those treatment naïve or experienced patients who had received SOF/LDV [24]. …”
Section: Discussionmentioning
confidence: 99%